HUBUNGAN ANTARA KETERAMPILAN MENGAJAR GURU DAN PRESTASI BELAJAR SISWA TUNARUNGU DI SMPLB-B DAN SMALB - Galuh Titian Sukma; Lena Nessyana Pandjaitan (Perpustakaan Universitas Surabaya, 2018)
the aim of this study was to detemire the correlation between teacher’s teaching skill and academic achivement towards deaf students. The participant for this study were 76 students which chosen by purposive sampling technique and based on students didn’t have mental retardation. This study was using teacher’s teaching skill questionare and daily exam score to measure student’s academic achievement. Data analysis for this study was performed with SPSS 20.0 for windows with Kendall’s core technique. The result of this studey find there in no significant relationship between teacher teaching skill and academic achievement, this study obtained sign of 0,988 (> 0,05) which means there is no significant correlation between teacher teaching skill and academic achievement towards deaf students. Academic achievement is not only relate with teacher teaching skill but ther is another factor that could influence academic achievement, like parent and friends factor. From this study, an advice that researcher could give was during the learning process, theacher can controll speed in speaking, so students can understand it well.